Stafne bone cyst: Report of a case and review of the literature - John Spencer Daniels; Ibrahim Albakry; Mohammed Ismail Samara; Ramat Oyebunmi Braimah (Saudi Journal for Health Sciences, 2020)
Stafne bone cyst is a rare and asymptomatic bone depression usually discovered incidentally on routine radiographs of the jaws. This pseudocyst could mimic odontogenic pathologies, especially sequelae of dental caries. We present a 25-year-old male with painful right mandibular swelling due to carious teeth on the right side of the mandible which the patient claimed was noticed 3 months prior to presentation. Panoramic radiograph showed grossly carious lower right first molar with periapical granuloma. In close relation with this, periapical pathology was a rounded well-defined radiolucency below the inferior alveolar canal. The patient had an extraction of the right lower first molar and was prescribed antibiotics. The apical pathology resolved completely after the extraction. A diagnosis of Stafne bone cyst was made as incidental finding following further investigation of the radiolucency below the inferior alveolar canal with computed tomographic scan.